Democracy, Culture, Catholicism : Voices from Four Continents - Crowley-Buck, John; Schuck, Michael Joseph, 1953- (Book collections on Project MUSE., 2016)
The dynamic interplay of democracy, culture, and Catholicism in the contemporary world is analyzed in twenty-three essays focused on four diverse countries: Indonesia, Lithuania, Peru, and the United States. The three-way relationship between democracy, culture, and Catholicism in these countries refracts in multiple directions. Each offers instructive comparisons and contrasts regarding the relationship between politics, civil society, and religion worldwide.